Effectiveness of Whole Brain Teaching Style in Enhancing the Academic Performance of Grade 11 Students in General Chemistry I - Abrenica, Jennilee; Casuncad, Jan Darell (SEAMEO QITEP in Science, 2022)
Abstract – This study aimed to determine the effectiveness of Whole Brain Teaching (WBT) Style in enhancing the academic performance of students of Don Ramon E. Costales Memorial National High School, Villasis, Pangasinan, Philippines in General Chemistry I. These were the findings: (1) WBT Style is an effective instructional strategy which enhanced the academic performance of students in General Chemistry I. (2) There was a significant difference between the performance of students taught using WBT Style and students taught using the traditional method in terms of their posttest mean scores (3) There was a significant difference in the mean scores change of the students after the WBT style was done. Results of the study showed that students enjoyed the WBT style of teaching. They also said that it was a fun method and it kept them alert in class. The students preferred the WBT style than the usual lecture-discussion type of teaching. Keywords – Whole Brain Teaching, academic performance, effectiveness, mean scores, science curriculum, General Chemistry I, pretest, posttest